2005
DOI: 10.1080/01443610500171250
|View full text |Cite
|
Sign up to set email alerts
|

Breast-feeding, return of menses, sexual activity and contraceptive practices among mothers in the first six months of lactation in Onitsha, South Eastern Nigeria

Abstract: The objective of this study was to determine the exclusive breast-feeding practices, return of menstruation, sexual activity and contraceptive practices among breast-feeding mothers in the first six months of lactation. The study was based in Onitsha, South Eastern Nigeria. A structured questionnaire was used to obtain data from breast-feeding mothers on their age, educational attainment, breast-feeding practices, return of menstruation, sexual activity and contraceptive practices within the first six months o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 8 publications
1
25
0
1
Order By: Relevance
“…29 In Onitsha (South-East Nigeria), 100% of mothers had established breastfeeding in their newborns before been discharged from the hospital. 30 At six and fourteen weeks visits for post-natal care, the rate was still impressive -81.4% and 74.7% respectively. At about the sixth month, however, the rate had gone as low as 3.9%.…”
Section: Description Of Reviewed Papers and Sample Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…29 In Onitsha (South-East Nigeria), 100% of mothers had established breastfeeding in their newborns before been discharged from the hospital. 30 At six and fourteen weeks visits for post-natal care, the rate was still impressive -81.4% and 74.7% respectively. At about the sixth month, however, the rate had gone as low as 3.9%.…”
Section: Description Of Reviewed Papers and Sample Characteristicsmentioning
confidence: 99%
“…In contrast, three reviewed studies found that the rate of "any breastfeeding" decreased as infant age increased. 24,30,35 This variation in results may be linked with bias associated with the use of inappropriate study designs as argued by Juaid, Binns, Giglia. …”
Section: Any Breastfeedingmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result the duration of lactational amenorrhea is declining, with the shortest periods being found in Eastern and Southern Africa (Ndugwa et al 2011). This change has been accompanied by a decline in postpartum abstinence, particularly in urban areas (Egbuonu et al 2005;Ndugwa et al 2011). Anthropologists have described how in Eastern Africa the post-partum period of abstinence was "eroded from within" by coitus interruptus (Schoenmackers et al 1981).…”
Section: Birth Spacing In Sub-saharan Africamentioning
confidence: 99%